2015
DOI: 10.1007/s11356-015-5589-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gametophyte physiology of Pteris multifida induced by the leaf leachate treatment of the invasive Bidens pilosa

Abstract: In recent years, the response of fern gametophytes to environment has raised much attention. However, studies on the influence of plant invasion to fern gametophytes are scarce. Allelopathy plays an important role in biological invasion. Hence, it is necessary to study the allelopathic effects of invasive plants on fern gametophytes and elucidate the mechanisms by which invasive plants cause phytotoxicity. As one of the main invasive plants in China, Bidens pilosa exhibits allelopathic effects on spermatophyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
11
0
2
Order By: Relevance
“…Field competition studies conducted by Ng et al [56] showed that BPr was dominant in groups consisting of Poaceae and C3 plants in competition with monoculture and polyculture groups of sixteen species. Likewise, BP and BPr have been found to possess phytotoxic effects on its sympatric plant species, such as Bidens bipinnata L. and Pteris multifida Poir., in the ecosystems [21,22]. In southeast Asia, BP and BPr have been investigated for their capability in paddy weed management.…”
Section: The Influence Of B Pilosa Var Radiata On the Reproduction mentioning
confidence: 99%
See 1 more Smart Citation
“…Field competition studies conducted by Ng et al [56] showed that BPr was dominant in groups consisting of Poaceae and C3 plants in competition with monoculture and polyculture groups of sixteen species. Likewise, BP and BPr have been found to possess phytotoxic effects on its sympatric plant species, such as Bidens bipinnata L. and Pteris multifida Poir., in the ecosystems [21,22]. In southeast Asia, BP and BPr have been investigated for their capability in paddy weed management.…”
Section: The Influence Of B Pilosa Var Radiata On the Reproduction mentioning
confidence: 99%
“…Bip. ( BPr ) was studied for its significant allelopathic inhibition effects on many plant species [ 19 , 20 , 21 , 22 ]. Xuan et al [ 23 ] indicated that 301 compounds (including polyacetylenes, flavonoids, phenolic acids, terpenes, fatty acids, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…This could be a positive response of L. formosana to slight oxidative stress. However, when the stress level reached a certain threshold, excessive accumulation of reactive oxygen species resulted in the inhibition of SOD activity [46,47]. However, the SOD activity increased only when the concentration of aqueous pericarp and rhizosphere soil extracts was 10 and 0.5 mg mL −1 , respectively, the other treatments inhibited the SOD activity, but the MDA content was elevated, indicating that the plasma membrane of L. formosana seedlings was damaged to varying degrees; however, L. formosana did not exhibit damage, indicating that these seedlings independently regulated stress levels through other antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Bidens pilosa é uma invasora bastante agressiva, cuja reprodução ocorre via sementes, possui crescimento rápido e pode ser encontrada durante todo o ano, mas as maiores infestações ocorrem durante a primavera e verão. Estudos recentes têm demonstrado que os efeitos prejudiciais de B. pilosa ocorrem com a liberação de aleloquímicos das folhas, parte aérea, exsudação pelas raízes e emissão de compostos voláteis para a rizosfera, os quais impedem a germinação e o estabelecimento de plântulas de outras espécies (Zhang et al 2016).…”
Section: Introductionunclassified
“…Bidens pilosa é uma invasora bastante agressiva, cuja reprodução ocorre via sementes, possui crescimento rápido e pode ser encontrada durante todo o ano, mas as maiores infestações ocorrem durante a primavera e verão. Estudos recentes têm demonstrado que os efeitos prejudiciais de B. pilosa ocorrem com a liberação de aleloquímicos das folhas, parte aérea, exsudação pelas raízes e emissão de compostos voláteis para a rizosfera, os quais impedem a germinação e o estabelecimento de plântulas de outras espécies (Zhang et al 2016).Muitas plantas medicinais apresentam efeito alelopático, e este pode ser direto ou indireto, danoso ou benéfi co, que uma planta exerce sobre outra pela produção de compostos químicos liberados no ambiente. A atividade dos aleloquímicos tem sido usada como alternativa ao uso de herbicidas, inseticidas e nematicidas, cujo uso intensivo e indiscriminado pode representar implicações…”
unclassified